Involvement of the subthalamic nucleus in engagement with behaviourally relevant stimuli. - Sauleau, P; Eusebio, A; Thevathasan, W; Yarrow, K; Pogosyan, A; Zrinzo, L; Ashkan, K; Aziz, T; Vandenberghe, W; Nuttin, B; Brown, P (2009)
In this study we investigate how the basal ganglia (BG) may process the behavioural relevance of environmental cues by recording local field potentials (LFPs) in the subthalamic nucleus of patients with Parkinson's disease who had undergone implantation of electrodes for deep brain stimulation. Fourteen patients were recorded as they performed a paradigm dissociating warning cue presentation from programming related to execution of specific tasks. Target and non-target warning cues of differing behavioural relevance were contrasted, and we evaluated if warning cue-evoked activities varied according to whether the eventual task to be performed was motor or cognitive and whether patients were receiving or withdrawn from dopaminergic therapy. Warning cues evoked a complex temporal sequence of activities with three epochs over the 760 ms following the onset of the warning cue. In contrast to the initial evoked LFP, evoked activities over two later periods were significantly influenced by behavioural relevance and by treatment state. The early activity was likely related to the initial orientating of attention induced by a novel target, while the delayed responses in our paradigm may reflect processing related to the non-motor resource implications of cues. The results suggest that the BG are intimately involved in the evaluation of changes in the environment and of their behavioural significance. The latter process is partly modulated by dopamine. Weakness in this function might contribute to the behavioural impairment that can follow BG lesions and surgery.